2018
DOI: 10.14254/2071-8330.2018/11-1/16
|View full text |Cite
|
Sign up to set email alerts
|

Innovation performance and R&D expenditures in Western European regions: Divergence or convergence?

Abstract: Although Western Europe is a global leader in innovation activities among the OECD countries, these activities are not distributed evenly across NUTS 2 regions. Thus, the analysis of convergence or divergence related to innovation performance and R&D expenditures among Western European NUTS 2 regions is posed as the aim of this paper. Applying differential local version of spatial autocorrelation (LISA), difference-in-difference estimation the paper reveals the local variation of convergence and divergence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…DEA and structural modelling were combined, where the DEA efficiency scores were used in the second step of the structural modelling (which is sometimes criticized in the literature; please refer to [34]). In another study, 178 NUTS-2 regions (for Western Europe) were compared using a mixed spatial autoregressive model and difference in differences (DID) approach (years included were 2007, 2009, and 2011) [35]. The results indicated that an innovation intensity divergence exists between the examined regions.…”
Section: Related Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…DEA and structural modelling were combined, where the DEA efficiency scores were used in the second step of the structural modelling (which is sometimes criticized in the literature; please refer to [34]). In another study, 178 NUTS-2 regions (for Western Europe) were compared using a mixed spatial autoregressive model and difference in differences (DID) approach (years included were 2007, 2009, and 2011) [35]. The results indicated that an innovation intensity divergence exists between the examined regions.…”
Section: Related Literature Overviewmentioning
confidence: 99%
“…Each row in both matrices represents the DMU j, with x o = (x 1o , x 2o , ..., x mo ) and y o = (y 1o , y 2o , ..., y so ) , and x o ≥ 0, x o 0 and y o ≥ 0, y o 0. The slacks-based measure (SBM) model was developed in [34,35] and is the approach used in this study. The reason for this is the fact that it has advantages when compared to the most used models, namely the Charnes-Cooper-Rhodes (CCR) and Banker-Charnes-Cooper (BCC) models; the SBM is an additive model with unit invariance properties and the possibility of being non-oriented and non-radial.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…For focused analyses, see e.g. Bednář and Halásková (2018), Prokop and Karbowski (2018) or Romer (1990).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dependent variable ( ) exhibits strong positive spatial autocorrelation when tested using the Moran's I statistic (for definition and application examples, see e.g. Bednář and Halásková, 2018). However, the spatio-temporal semivariogram (STSV) as per equation (3) can be used for a convenient description and visualization of both spatial and temporal variability aspects in observed data.…”
Section: Datamentioning
confidence: 99%
“…The problem of ensuring economic security of the country is one of the key aspects in the macroeconomic policy of developed and developing countries of the world (Bednar and Halaskova, 2018;Bhowmik, 2018;Fashina et al, 2018;Lyeonov et al, 2018;Milovic and Jocovic, 2017;Nguedie, 2018;Soylu et al, 2018;Vasylieva et al, 2018). The economic security of the state characterizes the condition of the national economy, which protects national interests, resistance to internal and external threats, the ability to develop and protect the vital interests of people, society, and the state.…”
Section: Introductionmentioning
confidence: 99%